SOSIALISASI DAN KONSULTASI HUKUM BISNIS, HUKUM KEWARGANEGARAAN, HUKUM PIDANA DAN HUKUM ADAT & MASYARAKAT DI KLINIK HUKUM INTERAKTIF RADIO SUARA JANGER POLDA BALI - DHARMAWAN, NI KETUT SUPASTI; WAIROCANA, I GUSTI NGURAH; SUDIARTA, NI KETUT; ARYANI, NYOMAN MAS; SATYAWATI, NI GUSTI AYU DYAH (Buletin Udayana Mengabdi, 2012)
ABSTRACT The team lecturers from Faculty of Law socialized Business law, Nationality law, Criminal law and Adat law at the Legal Clinic Radio Polda “SUARA JANGER” on July 2007. This community services used interactive method by using telephone, SMS and e-mail. The all session of interactive legal consultation were well done and got positive response from the communities as proven by the receipt of 4 to 5 calls within a one hour interactive duration conducted once a week. Through this services community and legal consultation several legal issues such as industrial design, children’s protection who were born from mix marriage, good governance, money laundering, terrorism, and polygamy were discussed and the further legal solutions were advised by the team advisors refer to the Act No. 31 year 2000, the Act No. 12 year 2006, and the Act No.15 year 2003.